Girsanov theorem for stochastic flows with interaction - Malovichko, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We prove an analog of the Girsanov theorem for the stochastic differential equations with interaction dz(u,t) = a(z(u,t),μt)dt + ∫R f(z(u,t)−p)W(dp,dt), where W is a Wiener sheet on ℝ × [0; +∞) and a(∙) is a function of special type.